Preoperative needed and received information in patients undergoing thoracic surgery in Bangladesh - Nasima Akter (Prince of Songkla University Faculty of Nursing (Nursing Science International Program), 2013)
Thesis (M.N.S., Nursing Science)--Prince of Songkla University, 2010